Evidence-based pharmacotherapy in cardiology. National guideline - S. Yu. Martsevich; N. P. Kutishenko; Yu. V. Lukina; V. V. Yakusevich; S. N. Tolpygina; I. V. Samorodskaya; M. M. Lukyanov; A. V. Zagrebelny; V. A. Metelskaya; E. A. Poddubskaya; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2024)
.